2014
DOI: 10.1021/bi500086p
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Deacetoxycephalosporin C Synthase Support a Consensus Mechanism for 2-Oxoglutarate Dependent Oxygenases

Abstract: Deacetoxycephalosporin C synthase (DAOCS) catalyzes the oxidative ring expansion of penicillin N (penN) to give deacetoxycephalosporin C (DAOC), which is the committed step in the biosynthesis of the clinically important cephalosporin antibiotics. DAOCS belongs to the family of non-heme iron(II) and 2-oxoglutarate (2OG) dependent oxygenases, which have substantially conserved active sites and are proposed to employ a consensus mechanism proceeding via formation of an enzyme·Fe(II)·2OG·substrate ternary complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 69 publications
3
50
0
Order By: Relevance
“…1E). A DAOCS⅐2OG⅐substrate ternary complex is proposed to react with O 2 to form a ferryl intermediate that initiates the reaction (32). One hydrogen atom is abstracted from the C2 ␤-methyl group of the substrate to produce a methylene radical, which undergoes rearrangement leading to ring expansion with the radical repositioned to the ternary carbon (C3), and then desaturation completes the reaction, perhaps by hydrogen atom transfer to the Fe(III)-OH (20,78).…”
Section: Other Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1E). A DAOCS⅐2OG⅐substrate ternary complex is proposed to react with O 2 to form a ferryl intermediate that initiates the reaction (32). One hydrogen atom is abstracted from the C2 ␤-methyl group of the substrate to produce a methylene radical, which undergoes rearrangement leading to ring expansion with the radical repositioned to the ternary carbon (C3), and then desaturation completes the reaction, perhaps by hydrogen atom transfer to the Fe(III)-OH (20,78).…”
Section: Other Reactionsmentioning
confidence: 99%
“…Carbapenem synthase (CarC) is used to describe both desaturation and epimerization reactions (29,30). Ring expansion by deacetoxycephalosporin C synthase (DAOCS) (31,32), epoxidation by hyoscyamine 6␤-hydroxylase (H6H) (33), and endoperoxide formation by FtmOx1 acting on fumitremorgin B (34) are also briefly described.…”
mentioning
confidence: 99%
“…27 Also it has been shown that DAOCS does, in fact, form a ternary complex in line with the general mechanistic strategy presented above. 48 …”
Section: General Mechanistic Strategy Of Non-heme Feii Enzymesmentioning
confidence: 99%
“…An in vitro process to carry out such a reaction would require the exogenous supply of 2OG that is a cost burden to the process; in addition the accumulation of the coproduct succinate could inhibit the bioconversion rate of the process (9). An in vivo process using E. coli as a whole-cell catalyst can provide an ideal solution to these problems because 2OG can be supplied in E. coli cells, and succinate will automatically be consumed without accumulation, thus effectively removing its inhibition of the DAOCS catalyzed reaction.…”
Section: The Effects Of Combining the Beneficial Mutations On G-7-adcamentioning
confidence: 99%
“…Several structures of DAOCS had been reported (7,8). Presteadystate kinetics and binding studies of DAOCS (9) suggested that DAOCS employs a mechanism similar to other 2OG-dependent oxygenases, where the binding of 2OG occurs first with subsequent formation of a ternary DAOCS·Fe(II)·2OG·penicillin substrate complex (9). The natural substrate of DAOCS is penicillin N, and its activity toward other penicillin analogs, such as penicillin G, is low (4).…”
mentioning
confidence: 99%